An Irregular School - Introduction of "Freie Schule in Berlin" Alternative School (Training and Practice : Journal of Educational Sciences, 2012)
The methodology of the alternative school, Freie Schule, in Berlin is still based on a concept that was typical among alternative schools at the beginning. According to this concept outer rules are completely unnecessary since it helps students in constructing their own inner rules. Realizing that the complete lack of rules cannot bring constructive results, alternative schools in general developed their practice in time. With the help of certain rules introduced they managed to frame school life. Why Freie Schule in Berlin has not changed this radically alternative practice yet? What can be the result of omitting rules in school life? How can the basic concept of order, freedom or chaos be interpreted? In my study I would like to present the results of a three-month qualitative research, made in Freie Schule in Berlin.